Customized structural and mechanical characteristics of Eu3+ imbued boro-telluro-dolomite glasses: effect of Dy3+ co-doping - Ibrahim Bulus; Areej S. Alqarni; Abd Rahman Tamuri; S. K. Ghoshal; Ibrahim Mohammed Danmallam; Abdullahi Anderson Kassimu (Journal of Taibah University for Science, 2023)
Inorganic oxide glasses with high mechanical strength and durability became demanding. Thus, a new type of Eu3+/Dy3+ co-doped boro-telluro-dolomite glass system with customized structures and mechanical properties were prepared by the melt-quenching method and characterized. The densities, FTIR and Raman spectra of the glasses revealed a significant modification in the network structure with the increase of Dy3+ contents. The values of microhardness and elastic moduli of the glasses were increased with the increase of co-doping contents. In addition, a correlation between the glass hardness and applied load was established. The proposed glasses were shown to withstand about 300 g applied force without any distortion, confirming their usefulness to design mechanically stable screen shield and high strength surfaces.